Correlation of striatal dopamine D2/3 receptor availability with GABA level in the anterior cingulate cortex in healthy controls but not in alcohol‐dependent subjects and individuals at high risk: A multimodal magnetic resonance spectroscopy and positron emission tomography study - Spitta, Gianna; Gleich, Tobias; Rosenthal, Annika; Schubert, Florian; Aydin, Semiha; Heinz, Andreas; Buchert, Ralph; Gallinat, Jürgen (Addiction biology, 2024)
Background The association of impaired dopaminergic neurotransmission with the development and maintenance of alcohol use disorder is well known. More specifically, reduced dopamine D2/3 receptors in the striatum of subjects with alcohol dependence (AD) compared to healthy controls have been found in previous studies. Furthermore, alterations of gamma‐aminobutyric acid (GABA) and glutamate (Glu) levels in the anterior cingulate cortex (ACC) of AD subjects have been documented in several studies. However, the interaction between cortical Glu levels and striatal dopamine D2/3 receptors has not been investigated in AD thus far. Methods This study investigated dopamine D2/3 receptor availability via 18F‐fallypride positron emission tomography (PET) and GABA as well as Glu levels via magnetic resonance spectroscopy (MRS) in 19 detoxified AD subjects, 18 healthy controls (low risk, LR) controls and 19 individuals at high risk (HR) for developing AD, carefully matched for sex, age and smoking status. Results We found a significant negative correlation between GABA levels in the ACC and dopamine D2/3 receptor availability in the associative striatum of LR but not in AD or HR individuals. Contrary to our expectations, we did not observe a correlation between Glu concentrations in the ACC and striatal D2/3 receptor availability. Conclusions The results may reflect potential regulatory cortical mechanisms on mesolimbic dopamine receptors and their disruption in AD and individuals at high risk, mirroring complex neurotransmitter interactions associated with the pathogenesis of addiction. This is the first study combining 18F‐fallypride PET and MRS in AD subjects and individuals at high risk. This is the first study combining 18F‐fallypride PET and MRS in AUD. We were able to show a negative correlation of GABA levels in the ACC with dopamine D2/3 receptor availability in the associative striatum in healthy controls. However, this association was not present in individuals at high‐risk and recently detoxified AD patients, which may reflect regulatory cortical mechanisms that seem to be altered, hypothetically due to dispositional factors or excessive alcohol intake.